Need Analysis Toward Development of Áqliyyah Nafsiyyah Taxonomy for Islamic Education Learning at Secondary Level - Husnul Rita Binti Aris; Saedah Binti Siraj; Zaharah Hussin (al-Afkar, Journal For Islamic Studies, 2024)
The purpose of the study is to investigate teacher’s view towards the need of developing Áqliyyah-Nafsiyyah Taxonomy Islamic Education learning for Secondary level. Model McKilip (1987) adapted was used as a basic model for the study. Method by using structured interview among 10 teachers teaching Islamic subject and 2 lecturers in Islamic education to investigate the need of development a new taxonomy. The data obtained were analyzed through thematic analysis by using Atlas. The overall findings show that mostly teachers and lecturers had agreed that the need of a new taxonomy for Islamic education for the future beside referring to Bloom taxonomy or other taxonomy which are not suitable for Islamic education right now. The result has shown the objective for need analysis in this phase had obtained. Twelve research participants' analysis results identified a need for a new taxonomy for secondary-level Islamic education learning, as the current approach relies solely on Bloom's taxonomy. The study is divided into eight parts: demographics of the participants, the meaning and importance of reason, how reason guides belief in Allah, the role of Islamic scholars, differences between Islam and the West, views on using Bloom's taxonomy in Islamic education, and the need for a new taxonomy. The study participants are classified by gender, age, teaching experience, positions held, and education levels.